From Listening to Producing : Ustaz Abdul Somad’s Active Audiences in Pekanbaru, Indonesia - Rosidi, Imron; Rajab, Khairunnas; Kasmuri, Kasmuri; Abduh, M. Arrafie; Masduki, Masduki (Universitas Islam Negeri Mataram, 2024)
The emergence of popular preachers in Indonesia today has colored the public sphere. This article aims to discover Ustaz Abdul Somad's audience's response to the da'wah (Islamic peaching) he delivered. This article uses a qualitative method by interviewing ten selected informants using a purposive sampling technique. This study finds that some of Ustaz Abdul Somad's audiences are active. They not only listen to Ustaz Abdul Somad's lectures but also produce video lectures that are distributed through social media. The popularity of preachers such as Ustaz Abdul Somad is supported by the activeness of his audiences and advances in communication technology. The popularity of Ustaz Abdul Somad indicates that widespread Islamization in Muslim societies continues to be carried out amid the onslaught of modernization and globalization. This article recommends that the role of audiences is crucial in spreading a preacher's popularity in Indonesia. This article also helps explain that today's da'wah audiences are very different from those in the past in term of active involvement in spreading the da’wah message.